IDEASIONAL FUNCTION TRANSITIVITY IN THE TEXT OF DAQAAIQUL AKHBAR: SYSTEMIC FUNCTIONAL LINGUISTIC STUDY - Juramli, J (Warmadewa University, 2017)
This paper reports condition of transitivity system of ideational function realized in the text of Daqaaiqul Akhbar, as a useful form of local cultural text that can nurture creativity of Sasak ethnic group. Investigation in this research was carried out with some focuses as fomulated in the research questions, such as 1) âWhat is the most dominant type of transitivity system realized in the text of Daqaaiqul Akhbar